Industrial Tourism in Small and Medium-Sized Industrial Enterprises: Challenges and Opportunities - Montenegro, Z.; Marques, J.; Sousa, C. (Proceedings of the 8th International Conference on Tourism Research, 2025)
This paper explores Industrial Tourism (IT) within Portuguese small and medium-sized enterprises (SMEs). It aims to identify the main challenges and opportunities of this tourism product and offers suggestions to enhance the sustainability and competitiveness of these organizations. This research seeks to understand the perspective of active industrial enterprises, or the "living industry," and how this type of tourism can enhance their sustainability and competitiveness. Primary data was collected through a questionnaire administered to 186 SMEs in Portugal. The findings show that most Portuguese SMEs do not engage in IT, mainly due to logistical, security, and strategic concerns. However, the study concludes that IT offers opportunities for SMEs to improve their marketing approaches, societal relationships, business strategies, and human resources.